Student's dietary - Alspaugh, Eva (My University, 1908)
Introduction: Herein is given data showing the dietary of three students, two girls and one boy. This is not intended to be a standard dietary, but simply shows the ordinary diet. The girls did their own cooking, and hence because of heavy college work, prepared many of the meals hastily, as , probably the menus will suggest.
Citation: Alspaugh, Eva. Student's dietary. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Diet; Nutrition; Health; Cooking; Handwritten; Graduating theses; Senior theses; Theses